Comparison of glucose‐lowering agents after dual therapy failure in type 2 diabetes: A systematic review and network meta‐analysis of randomized controlled trials. Issue 4 (8th January 2018) - Zaccardi, Francesco; Dhalwani, Nafeesa N.; Dales, Jolyon; Mani, Hamid; Khunti, Kamlesh; Davies, Melanie J.; Webb, David R.
Abstract : Aims: To assess the evidence supporting the choice of third‐line agents in adults with inadequately controlled type 2 diabetes. Materials and methods: We searched randomized controlled trials (RCTs) published between January 2000 and July 2017 that reported data on cardiometabolic outcomes and hypoglycaemia for glucose‐lowering agents added to metformin‐based dual treatments. Data were stratified by background therapy and RCT duration, and synthesized, when possible, with network meta‐analyses. Results: A total of 43 RCTs (16 590 participants) were included, with metformin combined with: sulphonylureas (SUs) in 20 RCTs; thiazolidinediones (TZDs) in 10; basal or rapid‐acting insulin in 6; dipeptidyl peptidase‐4 (DPP‐4) inhibitors in 3; glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) in 2; and sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors in 2. When added to metformin and SUs, after 24 to 36 weeks, rapid‐acting insulin resulted in the largest reduction in glycated haemoglobin (HbA1c; 1.6% vs placebo), followed by GLP‐1RAs (1.0%), basal insulin (0.8%) and SGLT‐2 inhibitors (0.7%), with no difference between GLP‐1RAs and SGLT‐2 inhibitors; body weight increased with insulin treatment ( 3 kg vs placebo), while the greatest reduction was observed for SGLT‐2 inhibitors compared with all other therapies. Limited data for hypoglycaemia indicated a similar risk for SGLT‐2 inhibitors and GLP‐1RAs. Results for third‐line agents added to metformin and TZDs were comparable, showing similar HbA1c reduction and risk of hypoglycaemia between SGLT‐2 inhibitors and GLP‐1RAs, and a slightly greater reduction in body weight with SGLT‐2 inhibitors vs GLP‐1RAs. Data for 52 to 54 weeks were more limited: added to metformin and a SU, TZDs, GLP‐1RAs or SGLT‐2 inhibitors reduced HbA1c to a similar extent but had different effects on body weight (7 kg and 5 kg more with TZDs vs SGLT‐2 inhibitors and GLP‐1RAs, respectively; 2 kg less when comparing SGLT‐2 inhibitors with GLP‐1RAs). Formal analyses could not be performed for any other dual therapy failure combinations because of the small number of available RCTs. Conclusions: Moderate‐quality evidence supports the choice of a third‐line agent only in patients on metformin combined with a SU or a TZD, with SGLT‐2 inhibitors performing generally better than other drugs. In suggesting third‐line agents, future guidelines should recognize the widely differing evidence on the various dual therapy failures.